(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
The article inform about origin of comparative linguistics,its development and difference between other types of comparative linguistics and also it discusses the problem of terminological differentiation of two disciplines as part of comparative linguistics, studying related languages in diachronic (compare historical linguistics) and in synchrony; for terminological marking of the second In this direction, the term "comparative synchronic linguistics" is introduced.